Large-scale slumping deduced from structural and sedimentary features in the Lower Palaeozoic Anglo-Brabant fold belt, Belgium - Debacker, T.N.; Sintubin, Manuel; Verniers, J. (Journal of the Geological Society, 2001)
Distinguishing slump folds From tectonic folds in poorly exposed areas can be difficult, especially when the scale of the slump folds exceeds outcrop scale. In the southeastern part of the single-phase deformed, Lower Palaeozoic Anglo-Brabant fold belt a comparison of cleavage/fold relationships and stratigraphic polarity shows that a 200 m thick interval of middle Caradoc fine-grained turbidites in the core of a large synform was overturned prior to tectonic deformation. This overturning is attributed to large-scale slumping, which was most likely a result of middle Caradoc seismic activity. status: Published